A cone-beam computed tomographic study of root and root canal morphology of primary maxillary and mandibular second molars in Indian Children: An in vitro study - Farhin Katge; Uma B Dixit (Wolters Kluwer Medknow Publications, 2022)
Introduction: The root canal system in primary molars is considered to be complex. The aim of the present study was to assess the morphology of roots and root canals of primary maxillary and mandibular second molars using the cone-beam computed tomography (CBCT). Materials and Methods: From a total of 104 collected primary maxillary and mandibular molars (51 maxillary second molars and 53 mandibular second molars), 60 teeth (30 each of maxillary and mandibular second molars) were selected randomly and accordingly assigned into two groups: MAX2M (primary maxillary second molars) and MAN2M (primary mandibular second molars). CBCT was used to assess the number of roots and root canals, length of root, mesiodistal and buccolingual width of the canal, shape of the canal, and intercanal communications. Descriptive statistical analysis was performed using the SPSS software version 17.0. Results: The mandibular second molars showed the presence of two roots in 27 sample molars while the presence of three roots was observed in three MAN2M group. In these molars, all three roots exhibited Type I root canal configuration. The maxillary second molars exhibited three roots. A total of nine intercanal communications were seen in MAX2M group, whereas two communications were seen in MAN2M group. The palatal root in MAX2M group was more angulated (mean value: 127.21 ± 9.10) as compared to mesial (mean value: 95.39 ± 8.64) and distal roots (114 ± 11.24). Conclusion: The comprehensive knowledge of root and canal morphology of primary molars and anatomic variations is essential for successful endodontic therapy.